KEEFEKTIFAN METODE MENULIS BERANTAI BERBANTUAN MEDIA TIKTOK DALAM MENINGKATKAN KETERAMPILAN MENULIS NASKAH DRAMA - Mariam, Rizka; Suntoko, Suntoko; Hartati, Dian (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the effectiveness of the chain writing method assisted by TikTok media in improving drama script writing skills in class XI students of SMA Negeri 1 Klari. This research uses a nonequivalent control group design. The data processing techniques used in this study are normality, homogeneity, N-Gain, and hypothesis tests. The results of the study were analysed with SPSS version 29. Based on the results of the T-Test calculation, the significance score (2-tailed) < 0.01, which means < 0.05 so that Ha is accepted. Thus, the chain writing method assisted by TikTok media is effectively applied in the skill of writing drama scripts in class XI students of SMA Negeri 1 Klari.